Social and cultural determinants of psychiatric illness : presenting in an urban general hospital - Sakinofsky, Isaac (Department of Psychiatry and Mental Health, 2020)
In spite of these words to Martha Bernays, at that time his fiancee, Freud was for very long preoccupied with the analysis of patients from a Viennese middle- class practice a lone. It was out of this experience that he evolved his views of the origin of psychological symptoms from repression of stereotyped instinctual urges of childhood . These instinctual demands arose out of the patriarchal Viennese society.